Promoting high standards of care for women living with HIV: position statement from the Women Against Viruses in Europe Working Group. Issue 2 (21st November 2017) - Kowalska, JD; Aebi‐Popp, K; Loutfy, M; Post, FA; Perez‐Elias, MJ; Johnson, M; Mulcahy, F; ,
Abstract : Objectives: Gender‐related factors can influence management decisions, treatment outcomes and the overall long‐term wellbeing of people living with HIV (PLWH). The Women Against Viruses in Europe (WAVE) Working Group was established to promote the health and wellbeing of women living with HIV (WLWH). WAVE is part of the European AIDS Clinical Society (EACS) and organizes annual workshops to discuss different issues in the management of WLWH. Methods: In 2016, 34 WAVE members including community representatives, HIV clinicians and researchers met to discuss standards of care for WLWH and to review current guidelines. Participants focused on three different themes: (1) access to and engagement and retention in care; (2) monitoring of women on antiretroviral therapy and management of comorbidities; and (3) review of EACS treatment guidelines. Results: Five priority areas for optimizing the care of WLWH were identified: (1) psychosocial aspects of HIV diagnosis and care; (2) mental health and wellbeing; (3) pharmacokinetics, toxicity and tolerability of antiretroviral therapy; (4) coinfections and comorbidities; and (5) sexual and reproductive health. WAVE recommendations are provided for each of these areas, and gaps in knowledge and needs for changes in currently existing standards are discussed. Conclusions: This position statement provides an overview of the key recommendations to optimize the care of WLWH that emerged during the 2016 WAVE workshop.